Optimization of Whole Mount RNA Multiplexed in situ Hybridization Chain Reaction With Immunohistochemistry, Clearing and Imaging to Visualize Octopus Embryonic Neurogenesis - Elagoz, Ali M.; Styfhals, Ruth; Maccuro, Sofia; Masin, Luca; Moons, Lieve; Seuntjens, Eve (Frontiers in Physiology, 2022)
Gene expression analysis has been instrumental to understand the function of key factors during embryonic development of many species. Marker analysis is also used as a tool to investigate organ functioning and disease progression. As these processes happen in three dimensions, the development of technologies that enable detection of gene expression in the whole organ or embryo is essential. Here, we describe an optimized protocol of whole mount multiplexed RNA in situ hybridization chain reaction version 3.0 (HCR v3.0) in combination with immunohistochemistry (IHC), followed by fructose-glycerol clearing and light sheet fluorescence microscopy (LSFM) imaging on Octopus vulgaris embryos. We developed a code to automate probe design which can be applied for designing HCR v3.0 type probe pairs for fluorescent in situ mRNA visualization. As proof of concept, neuronal (Ov-elav) and glial (Ov-apolpp) markers were used for multiplexed HCR v3.0. Neural progenitor (Ov-ascl1) and precursor (Ov-neuroD) markers were combined with immunostaining for phosphorylated-histone H3, a marker for mitosis. After comparing several tissue clearing methods, fructose-glycerol clearing was found optimal in preserving the fluorescent signal of HCR v3.0. The expression that was observed in whole mount octopus embryos matched with the previous expression data gathered from paraffin-embedded transverse sections. Three-dimensional reconstruction revealed additional spatial organization that had not been discovered using two-dimensional methods.